2019
DOI: 10.3390/ijms20071608
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Receptor Gene is Essential for Chicken Mitochondrial Function In Vivo and In Vitro

Abstract: The growth hormone receptor (GHR) gene is correlated with many phenotypic and physiological alternations in chicken, such as shorter shanks, lower body weight and muscle mass loss. However, the role of the GHR gene in mitochondrial function remains unknown in poultry. In this study, we assessed the function of mitochondria in sex-linked dwarf (SLD) chicken skeletal muscle and interfered with the expression of GHR in DF-1 cells to investigate the role of the GHR gene in chicken mitochondrial function both in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…GHR ablation is detrimental to osteocyte and fibroblast mitochondrial function ( Liu et al, 2019 ). Consistently, mitochondrial function is impeded in the skeletal muscle of SLD chickens and GHR knockdown cells, indicating that GHR promotes mitochondrial function in vivo and in vitro ( Hu et al, 2019 ). However, these data are in conflict with a previous report that demonstrated an enhanced mitochondrial function in the liver, muscle, heart, kidneys, and brain of aged GHRKO mice ( Brown-Borg et al, 2009 ).…”
Section: The Effects Of Gh–ghr–igf1 Axis On Mitochondrial Functionmentioning
confidence: 91%
See 1 more Smart Citation
“…GHR ablation is detrimental to osteocyte and fibroblast mitochondrial function ( Liu et al, 2019 ). Consistently, mitochondrial function is impeded in the skeletal muscle of SLD chickens and GHR knockdown cells, indicating that GHR promotes mitochondrial function in vivo and in vitro ( Hu et al, 2019 ). However, these data are in conflict with a previous report that demonstrated an enhanced mitochondrial function in the liver, muscle, heart, kidneys, and brain of aged GHRKO mice ( Brown-Borg et al, 2009 ).…”
Section: The Effects Of Gh–ghr–igf1 Axis On Mitochondrial Functionmentioning
confidence: 91%
“…However, several recent findings are different from the previous results. Our previous study has revealed that the gene expression of mitochondrial biogenesis markers ( PGC1 α, NRF1 , and TFAM ) and mtDNA-encoded OXPHOS genes are all downregulated in the skeletal muscle of SLD chickens and GHR knockdown cells ( Hu et al, 2019 ). At the same time, we observed that the enzymatic activities of OXPHOS complexes (complexes I, II, III, and IV) are reduced in the skeletal muscle of SLD chickens and GHR knockdown cells, indicating that GHR exhibits a positive effect on mitochondrial biogenesis.…”
Section: The Effects Of Growth Hormone Receptor On Mitochondrial Biogmentioning
confidence: 99%
“…The production of reactive oxygen species (ROS) in the mitochondria of cells was measured using an ROS assay kit (Beyotime, China) according to the manufacturer's protocol. Dichlorofluorescein (DCF) fluorescence was determined using a Fluorescence/Multi-Detection Microplate Reader (BioTek, USA) as previously described [11]. Data were normalized to the control group and are expressed as a percentage of control levels.…”
Section: Detection Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Liver tissues were fixed in 2.5% glutaraldehyde for 4 h at 4°C and then cultured as previously described (Luo et al, 2016). Transmission electron microscope (Hitachi HT7700, Japan) was used to examine and photograph mitochondria, and five randomly selected areas were photographed at × 2500 magnification and counted as previously reported (Hu et al, 2019).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%